2021
DOI: 10.21203/rs.3.rs-775456/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental conditions drive self-organisation of reaction pathways in a prebiotic reaction network

Abstract: The evolution of life from the prebiotic environment required a gradual process of chemical evolution towards greater molecular complexity. Elaborate prebiotically-relevant synthetic routes to the building blocks of life have been established. However, it is still unclear how functional chemical systems evolved with direction using only the interaction between inherent molecular chemical reactivity and the abiotic environment. Here, we demonstrate how complex systems of chemical reactions exhibit well-defined … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…We have recently shown that product compositions of the formose reaction, a model prebiotic reaction system, are the result of inherent interaction between chemical reactivity and the environment. We found that the formose reaction creates compositional patterns in response to varying steady-state environmental conditions 19 . It produces a wide range of carbohydrate molecules (fig.…”
Section: Experimental Studies Of the Formose Reaction In A Dynamic En...mentioning
confidence: 85%
See 3 more Smart Citations
“…We have recently shown that product compositions of the formose reaction, a model prebiotic reaction system, are the result of inherent interaction between chemical reactivity and the environment. We found that the formose reaction creates compositional patterns in response to varying steady-state environmental conditions 19 . It produces a wide range of carbohydrate molecules (fig.…”
Section: Experimental Studies Of the Formose Reaction In A Dynamic En...mentioning
confidence: 85%
“…It produces a wide range of carbohydrate molecules (fig. S1) from the feedstocks formaldehyde (H2C=O, 1) and an initiator compound, such as dihydroxyacetone (DHA, 3), using metal hydroxides (for example, Ca 2+ and OH -) as catalysts [19][20][21][22][23] . A key characteristic of the formose reaction is that a limited set of reaction classes recursively operate on the feedstocks and their reaction products to create a combinatorial explosion of compounds (fig.…”
Section: Experimental Studies Of the Formose Reaction In A Dynamic En...mentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of monosaccharides can be generated via aldol reactions in the reaction pathways that branch out from the autocatalytic reaction cycle. Furthermore, various side reactions, such as the crossed Cannizzaro reaction that leads to the decomposition of monosaccharides, also comprise a large part of the entire reaction network 6,12 Fig. 1c).…”
Section: Introductionmentioning
confidence: 99%